Foreign direct investment & indigenization in zimbabwe's platinum sector: is the indigenization and economic empowerment act a deterrent to foreign investors? - Runganga, Desire (Centre for Law and Society, 2025)
Indigenization and the economic empowerment of historically disadvantaged communities is a delicate subject in many mining jurisdictions. This dissertation seeks to assess the effectiveness of Zimbabwe's indigenization laws in balancing the interests of foreign investors, host communities, the state and indigenous Zimbabweans at large. The dissertation acknowledges that the law concerning indigenization and economic empowerment in Zimbabwe has evolved and evaluates whether the cumulative amendments have been progressive in redressing the historical injustices done to indigenous Zimbabweans. Before any amendments, the legislation mandated all foreign investors to cede 51 per cent of their investments to indigenous Zimbabweans. The amendments lifted the requirement and made the indigenization laws exclusively applicable to the extractive sector. While the responsible Minister is yet to declare the minerals subject to the indigenization laws, the industry finds itself operating at the mercy of the Minister's discretion. This dissertation is premised on the idea that uncertainty is the primary factor that impedes FDI. The platinum sector is largely operated by foreign investors and was singled out together with the diamonds sector to be subject to indigenization laws in 2018 only to be exempted in 2021. The findings establish that the current framework disguises the regulation and implementation of state participation as indigenization. By doing so the State conflates two policies whose objectives are fundamentally divergent. One seeks to foster restorative justice and the other to enhance the State's share of the economic rents from mining. The former is an urgent cause, and the latter is a choice that can be foregone without serious consequences by merely adopting other tax tools. Consequently, the legislation creates an ambiguous policy direction and ultimately investor uncertainty. The research questions whether local parastatals can balance their fiduciary responsibilities to be loyal not only to the State but also to the foreign investor as a forced partner and whether indigenization is merely nationalisation. The dissertation concludes that the legal framework falls short of the tenets of empowerment. It further offers insight and recommendations on how the legislation burdens foreign investors with the need to implement ‘double indigenization policies' parallel to each other at an added expense. One to acquire the social license to operate and the other for purposes of attaining indigenization accreditation which is merely state participation.